Effectiveness of National Mission on Oilseed and Oil Palm on Adoption of Mustard Crop Interventions - Kumar, Amit; Bareth, LS; Yadav, JP; Ghaswa, Ramdhan (Indian Journal of Extension Education, 2025)
National Mission on Oilseed and Oil palm (NMOOP) for oilseeds & oil palm developmentÂ program in India was started in July 2014. The present study was conducted in the Bikaner district of Rajasthan. Bikaner district has been selected purposely because of Bikaner districtÂ has highest production of oilseeds (472026 tones) among all districts of the state. Further, two panchayat samities namely Lunkaransar and Khajuwala were selected based on highest area and production of these crops and NMOOP scheme was also operated in theseÂ panchayat samities. Two villages from each selected panchayat samiti were selected randomly where NMOOP activities have been in operations in the year 2014-15. FromÂ each village 20 beneficiaries and the equal number of non-beneficiary farmers were selected randomly. The findings revealed that majority of beneficiary and non-beneficiary farmers belonged to medium adoption category. It was found that there was a significant differenceÂ in level of adoption between beneficiary and non-beneficiary farmers about recommended interventions of mustard crop.